Policy change, dismantling and environmental protection in Brazil - Neves, Estela Maria Souza Costa (Sustainability in Debate, 2023)
This article investigates recent changes in the field of Brazilian environmental policy, exploring contributions from the international literature on policy dismantling as applicable to the Brazilian case. Federal environmental policy is analysed over four decades (1981-2021) in light of the structural characteristics of environmental policy from the perspective of dismantling as a process involving relative change, focusing on the trajectory of a specific policy. The systematic direction of the changes made to paralyse key activities and environmental legal enforcement, jeopardising areas and topics across the agenda during the 2016-2022 period, allows the characterisation of that ongoing process as the dismantling of environmental policy, extending to the entire environmental stewardship framework. There is a need to deepen investigations to understand the still-undetermined effects of this dismantling, such as their impact, the permanence of its effects in the medium term, and the spread of consequences beyond the environmental area, as well as its possible long-term impact on the democratic regime.